1991
DOI: 10.1200/jco.1991.9.10.1776
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of Wilms' tumor patients with pulmonary metastases detected only with computed tomography: a report from the National Wilms' Tumor Study.

Abstract: To evaluate the prognosis of patients with Wilms' tumor who have pulmonary densities identified on a computed tomographic (CT) scan of the chest, but have a negative plain chest radiograph, we reviewed the treatments and outcome of 32 patients randomized or followed on National Wilms' Tumor Study (NWTS)-3. The 4-year event-free and overall survival percentages of 18 of these patients who had a favorable histology tumor and were treated as stage IV tumors with three or four drugs plus whole-lung irradiation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Survival outcomes in children with CT-only disease have been described in the literature but in very small numbers [10,[13][14][15]17,18]. Wilimas et al [18] reported on 11 patients with favorable histology and a normal CXR and CT pulmonary lesion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Survival outcomes in children with CT-only disease have been described in the literature but in very small numbers [10,[13][14][15]17,18]. Wilimas et al [18] reported on 11 patients with favorable histology and a normal CXR and CT pulmonary lesion.…”
Section: Discussionmentioning
confidence: 96%
“…Computed tomography-only lesions have been the subject of reports from the NWTS Group [10,13,14,17]. In NWTS-3 and NWTS-4 children with favorable-histology tumors and pulmonary densities identified only by CT scan were treated either as stage IV or local regional disease stage [14,17].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for not recommending a CT scan of the chest are based on an article by Green et al published in 1991 [3]. In summary, these workers evaluated 27 patients with nodules detected on chest CT but not on chest radiograph.…”
Section: Ct Scan Of the Chestmentioning
confidence: 98%
“…First, some of the articles published by radiologists represent experience in single institutions and therefore lack adequate numbers of patients for meaningful analysis [1,2]. Second, several recent publications on the imaging of Wilms' tumor have not included any radiologists as co-investigators and authors and consequently have flaws in technique and analysis [3][4][5].…”
Section: Introductionmentioning
confidence: 97%
“…Available data suggest there are no significant differences between event-free and OS rates when computed tomography (CT) is used rather than chest radiography (CXR) for diagnosis of pulmonary lesions (5,6). However, the validity of studies justifying the use of only CXR has also never been verified, and available data are based on small, retrospective studies.…”
Section: Introductionmentioning
confidence: 96%